The Influence of Accounting Understanding and Characteristics on the Quality of Financial Statements of MSMEs Fostered by Bank Indonesia - Siti Nurdela Helingo; Harun Blongkod; Ayu Rakhma Wuryandini (Pt. Anagata Sembagi Education, 2024)
The purpose of this study is to gather empirical data regarding the impact of business attributes and accounting knowledge on the caliber of financial reports produced by MSME's. Quantitative techniques are used in this study model or design. 68 MSMEs registered with the Bank Indonesia Gorontalo Branch made up the population of this study, and 68 MSME respondents made up the sample. In this study, questionnaires and observation were employed as data gathering methods, while PLS-SEM analysis was employed as a data analysis method. The study's findings demonstrate that the quality of financial reports (Y) is positively impacted by both business characteristics (X2) and accounting understanding (X1). Amounting to 76.5%, this indicates that the variables Accounting Understanding (X1) and Business Characteristics (X2) can account for the Quality of Financial Reports (Y). In the meantime, other variables not covered in this study can account for the remaining 23.5%.